Intelligent Temperature Controller for Energy Storage System in Electric Vehicle Applications - Mannan M.; Al-Shetwi A.Q.; Fitriah Nor S.; Hannan M.A.; Jern K.P.; Rahman S.A.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Charging (batteries); Computer circuits; Controllers; Electric control equipment; Electric vehicles; Fuzzy logic; Global warming; Lithium-ion batteries; MATLAB; Proportional control systems; Storage management; Thermal management (electronics); Three term control systems; Battery energy storage systems; Carbon emissions; Fuzzy logic controllers; Performance; Proportional integral and derivatives; Proportional integral controllers; Proportional-derivative controllers; Storage systems; Temperature controllers; Vehicle applications; Temperature control